Prevalence of Ticks Infesting Dairy Cattle and the Pathogens They Harbour in Smallholder Farms in Peri-Urban Areas of Nairobi, Kenya - Shepelo Getrude Peter; Hellen Wambui Kariuki; Gabriel Oluga Aboge; Daniel Waweru Gakuya; Ndichu Maingi; Charles Matiku Mulei (Veterinary Medicine International)
This study aimed at determining the tick species infesting dairy cattle in Nairobi, Kenya, and the pathogens they harbour. While ticks are well-known vectors of major bacterial pathogens of both veterinary importance and public health importance, few studies have investigated the range of the tick species and the associated pathogens, especially present in unique dairy production systems, which compromise animal welfare, such as those in peri-urban areas. A cross-sectional study was undertaken involving 314 randomly selected dairy cattle in 109 smallholder farms. Each animal was examined for attached ticks followed by morphological tick identification at the species level. Genomic DNA was extracted from each of the ticks, and 16S rDNA gene was amplified for pathogen identification. Sequencing of the amplicons and subsequent BLASTn analysis, multiple sequence alignment, and phylogenetic reconstruction were performed to confirm the species of the pathogens. Sixty-six (21.0%) of the cattle examined had ticks. A total of 94 adult ticks were found on the cattle, and of these, 63 (67.0%), 18 (19.1%), and 13 (13.8%) were in the genera Rhipicephalus, Amblyomma, and Hyalomma, respectively. Twelve tick species in Rhipicephalus genus and two in Amblyomma and Hyalomma genera were identified. Although Rh. decoloratus was the most prevalent tick (24.5% (23/94)), the emerging Rh. microplus (6.4% (6/94)) was also identified. The DNA of Rickettsia was detected in the ticks, with Rickettsia conorii in H. rufipes and A. variegatum, and Rickettsia aeschlimannii in Rh. microplus and H. rufipes, while Ehrlichia ruminantium and E. canis were in A. variegatum. In conclusion, the study reported a wide range of tick species present in the study area including Rhipicephalus microplus, which is an emerging tick species in parts of Kenya. The ticks harboured DNA of Rickettsia and Ehrlichia, highlighting possible animal and human health concerns. Hence, effective tick control strategies remain paramount to prevent potential diseases associated with the harboured pathogens.